Design method of forest health-care footpath assembly
By designing a forest health trail combination with leaf layer with anticorrosion coating, a sandy and soil layer mixed with waste mask fragments, and a plain tamped layer of buried ground hotline, the problems of reduced forest health care and trail safety in winter have been solved, and stability and safety have been improved.
Patent Information
- Application Number
- CN202411782874.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In winter, the existing forest trails have reduced the relative content of monoterpenes, which lead to a reduced health care and wellness effect in forests. At the same time, the hardening treatment of trails and deciduous water accumulation affect safety.
A forest health trail assembly was designed, including a leaf layer with anticorrosion coating, a sandy and soil layer mixed with waste mask fragments, and a plain earth compaction layer buried with ground hotline. Through these layers of design, the release of beneficial gases is promoted in concert and the stability and safety of the trail are improved.
Maintain the natural ecology of the forest, improve the health care and wellness effects of forests and trails, enhance the stability and safety of the trails, and avoid the phenomenon of sand and soil liquefaction.
Smart Images

Figure CN119593273A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of forest trails, and in particular relates to a design method for a forest health trail assembly. Background Art
[0002] In recent years, people's awareness of environmental health care has been increasing, and it has become an inevitable trend to give full play to the ecological health care function of vegetation to improve physical health and improve the quality of life. As the main body of ecological construction, forests not only have multiple ecological benefits such as carbon fixation and oxygen production, maintaining atmospheric balance, conserving water sources, preventing wind and sand, and trapping dust and reducing noise, but also are ideal places for leisure and health care activities. The health care and recuperation function of forests mainly refers to the release and volatilization of substances beneficial to the human body by trees to achieve the purpose of improving immunity, preventing and treating diseases. Forest trails are strip leisure spaces that rely mainly on forests and are mainly based on hiking. They provide routes for hikers to appreciate and explore nature up close. As a physical place and experience carrier for implementing forest health care and recuperation, the construction of trail facilities should also be given a certain degree of attention.
[0003] A large number of studies have shown that among the volatile organic compounds released by plants, monoterpenes and sesquiterpenes have the greatest health-care effects. Therefore, the sum of the relative contents of monoterpenes and sesquiterpenes can be used as an indicator to measure the health-care effects of plants. According to this indicator, studies have shown that cypress, masson pine, and cryptomeria can be used as ideal health-care tree species. In addition, compared with cypress and masson pine, cryptomeria can maintain the relative content of monoterpenes at a higher level for a longer period of time in a year. Therefore, choosing cryptomeria forests as health-care tree species can enhance the health-care functions of forests and trails to a certain extent. However, the relative content of monoterpenes and other substances in these health-care tree species (including cryptomeria) is lower in winter due to the influence of temperature, moisture, etc., which further reduces the health-care and recuperation effects of the forest in this season.
[0004] At present, most forest trails have been artificially built and hardened, and the trails are decorated with fake leaves to achieve the purpose of beauty, resulting in heavy traces of artificial decoration, which has destroyed the original natural landscape of the forest to a certain extent. In order to maintain the original ecological landscape of the forest, some trails are mainly built in the form of mountain dirt roads without weeds, and non-hardened roads such as soil, grass, humus, and fallen leaves are advocated. These trails only simply pave the road surface, and do not carry out necessary treatment on the part below the road surface. The fallen leaves and grass on the road surface lack water permeability, which is prone to corruption and water accumulation. Especially in the case of continuous rain, the problems of road water accumulation and fallen leaf corruption will be further aggravated, thus affecting the safety of the trail. In addition, the soil under the pavement of some trails currently has sand with good water permeability. Even so, the ordinary sand layer will produce a certain "compaction" phenomenon after long-term trampling, which will have an adverse effect on its permeability and may cause the sand layer to liquefy, greatly increasing the risk factor of the trail. Summary of the invention
[0005] In response to the above-mentioned problems in the prior art, the technical problem to be solved by the present invention is a design method for a forest health trail combination, which aims to maintain the original natural ecology of the forest while designing a forest health trail combination that can cooperate with the forest to play a health care function. The combination includes a leaf layer with an anti-corrosion coating, a sandy soil layer mixed with discarded mask fragments, and a compacted soil layer for burying geothermal lines. The leaf layer can release beneficial gases, and the sandy soil layer and the soil layer respectively play their respective functions to jointly promote the release of beneficial gases.
[0006] The technical solution of the present invention is as follows:
[0007] A design method for a forest health trail combination, the forest trail is divided into three layers in total, including, from top to bottom, a leaf layer with an anti-corrosion coating, a sandy soil layer mixed with discarded mask fragments, and a rammed soil layer for burying geothermal lines, wherein the leaf layer is the above-ground layer, and the sandy soil layer and the soil layer are buried underground, that is, the sandy soil layer and the soil layer are both underground layers.
[0008] Preferably, the width of the trail is 1 to 1.5 m, and drainage ditches with a width of 8 to 10 cm and a slope height of 8 to 10 cm are designed on both sides of the trail.
[0009] Preferably, the leaf layer with the anti-corrosion coating is characterized in that the leaves are Cryptomeria fortunei leaves, the thickness of the leaf layer is 3 to 5 cm, and the anti-corrosion coating is a homemade Cu / ZnO-chitosan-pulullan coating.
[0010] Preferably, the Cu / ZnO-chitosan-pululan coating is characterized in that the coating preparation method comprises the following steps:
[0011] (1) Dissolving chitosan, pullulan and cinnamaldehyde in acetic acid solution, heating in a water bath at 58-65° C. with stirring for 2.5-3.5 h, to obtain a chitosan-pullulan solution; wherein the mass ratio of chitosan, pullulan and cinnamaldehyde is 1:(0.5-0.8):(0.35-0.45), the mass (g) of chitosan to the volume (mL) of acetic acid solution is 1:(95-105), and the volume fraction of the acetic acid solution is 1%;
[0012] (2) dissolving copper acetate and polyvinyl pyrrolidone in diethylene glycol, stirring under magnetic force at 48-52° C. for 28-32 min, adding whisker-like ZnO, and then slowly pouring into the thiourea solution, and simultaneously adding all the chitosan-pullulan solution prepared in step (1) and a small amount of glycerol, stirring at 115-125° C. for 28-32 min, and then cooling to 22-28° C. to obtain a Cu / ZnO-chitosan-pullulan mixed solution; wherein the mass ratio of copper acetate, polyvinyl pyrrolidone, and whisker-like ZnO is 1:(0.9-5.8):(4.8-5.2), and the ratio of thiourea volume (L):diethylene glycol volume (L):copper acetate mass (g):glycerol volume (L) is 1:(3.8-4.2):(1.8-10):(0.08-0.12);
[0013] (3) Soaking the Cryptomeria fortunei leaves in the Cu / ZnO-chitosan-pulullan mixed solution obtained in step (2) for 6 to 8 hours, and drying them at 22 to 28° C. for 22 to 26 hours to obtain Cryptomeria fortunei leaves with an antiseptic coating.
[0014] Preferably, the Cryptomeria fortunei leaves are fresh leaves.
[0015] Preferably, the sand layer mixed with discarded mask fragments is characterized in that the earrings and metal strips of the discarded masks have been removed and have been sterilized, and its main component is polypropylene; the fragment length is 12 to 15 mm and the width is 2 to 6 mm; the overall thickness of the sand layer is 20 to 30 cm, wherein the discarded mask fragments are mixed into the sand in an intermittently laid manner, that is, a layer of 2 to 3 cm compacted discarded mask fragments is laid on each layer of 2 to 3 cm compacted sand.
[0016] Preferably, the sterilization treatment of discarded masks is ultraviolet sterilization.
[0017] Preferably, the Cryptomeria fortunei leaves are immersed in the Cu / ZnO-chitosan-pullulan mixture. There is no specific requirement for the weight relationship between the Cryptomeria fortunei leaves and the Cu / ZnO-chitosan-pullulan mixture, as long as all the added Cryptomeria fortunei leaves can be immersed in the Cu / ZnO-chitosan-pululan mixture.
[0018] Preferably, the rammed earth layer for burying geothermal lines is characterized in that the soil is washed with clean water 1 to 3 times before laying, and the geothermal lines heat the soil only in winter (November to February of the following year), with a power of 1kw; the geothermal lines are buried at 1 / 2 of the depth of the soil layer, arranged in an S shape with 1 / 2 of the width of the trail, and the area where the geothermal lines are laid is of equal length from the edges of both sides of the trail; the temperature is controlled at 20 to 25°C with an automatic temperature controller, and the temperature control probe is inserted in the sand layer; the thickness of the rammed earth layer is 20 to 30cm.
[0019] Preferably, the area where the geothermal line is laid is of equal length from the edges of both sides of the trail, both being 0.25 to 0.38 m.
[0020] The ZnO in the present invention is in the form of whiskers.
[0021] The laying of the forest trail in the present invention can follow the principle of convenient ecological construction of the trail and ensuring the safety of hikers walking across it, while ensuring that the community structure of the Cryptomeria fortunei forest is not destroyed and the original natural ecology of the forest is maintained. Combined with the sampling and analysis results of the volatile components of the plants, the most suitable trail crossing route is selected and then the trail is laid.
[0022] The present invention can select the laying route of the forest trail in combination with the sampling and analysis results of the plant volatile components, wherein the sampling and analysis method of the plant volatile components is to install the air samplers of the dynamic headspace extraction device at the 1 / 3 and 2 / 3 positions of the crossing route respectively, use the air sampler to extract the plant volatile components, continue sampling for 3 to 5 hours, and use thermal desorption-gas chromatography / mass spectrometry to determine the relative content of monoterpenes and sesquiterpenes.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The road surface of the forest health trail assembly designed by the present invention is paved with leaves of Cryptomeria fortunei, forming a non-hardened road surface with a certain elasticity, which to a large extent maintains the original ecology of the forest and reduces interference with the environment. In addition, the Cryptomeria fortunei leaves on the trail can release volatile organic compounds such as monoterpenes, which are beneficial to human physical and mental health.
[0025] 2. In order to prevent the leaf layer from decaying too quickly, the present invention covers the surface with an anti-corrosion coating. In addition, in addition to improving the stability of the trail, the rammed earth layer of the trail is also designed with a heating device, which can appropriately increase the soil temperature when needed (for example, the low temperature and dryness in winter affect the release of beneficial gases such as monoterpenes). The water vapor formed under the cover of the Cryptomeria fortunei leaf layer on the soil surface increases the humidity of the environment around the leaves, promoting the release of beneficial gases such as monoterpenes. The existence of the sandy soil layer is conducive to the upward diffusion of water vapor generated by heating the soil layer in winter, and can also avoid water accumulation due to the heat and heat of fallen leaves in summer. In addition, heating the trail in winter can not only enhance the comfort of pedestrians when walking, but also enable the Cryptomeria fortunei trees around the trail to release more beneficial gases under heated and humid conditions, thereby improving the health and recuperation effects of the forest and trail as a whole.
[0026] 3. The present invention carries out special treatment on the part below the trail surface, and mixes the discarded mask fragments after disinfection into the sand layer, which improves the permeability and elasticity of the sand layer, thereby preventing the sand layer from being completely compacted to avoid the liquefaction of sand. In addition, the interfacial interaction between sand and fiber enhances the stability and bearing capacity of the sand, and improves the safety of the forest trail. In addition, the presence of the sand layer can reduce the probability of water reverse infiltration due to small soil pores, and the drainage ditch on both sides of the trail has a certain slope to form a reverse diffusion layer, which can effectively prevent water from reverse infiltration.
[0027] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a simulation of a forest trail;
[0029] Figure 2 , 3 It is the infrared spectra of Examples 1 to 3 and Comparative Example 2, wherein Figure 3 for Figure 2 A partial enlarged view of
[0030] Figure 4 The SEM images of the coating samples of Example 2 and Comparative Example 2 are shown;
[0031] Figure 5 The antibacterial test results of the coating samples of Examples 1 to 3 and Comparative Example 2 are shown;
[0032] Figure 6 The test results of moisture absorption performance of coating samples of Example 1, Example 3 and Comparative Example 2 are shown. DETAILED DESCRIPTION
[0033] The present invention is specifically described below by way of examples, which are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. It should be understood that after reading the contents of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
[0034] Example 1
[0035] A design method for a forest health trail combination, characterized in that the forest trail is divided into three layers in total, including, from top to bottom, a leaf layer with an anti-corrosion coating, a sand layer mixed with discarded mask fragments, and a rammed soil layer for burying geothermal lines. The leaf layer is on the ground, and the other two layers are buried underground. The trail is 1.2m wide, and in addition, drainage ditches with a width of 9cm and a slope height of 9cm are designed on both sides of the trail.
[0036] The leaves in the leaf layer with the anti-corrosion coating are Cryptomeria fortunei leaves, the thickness of the leaf layer is 4 cm, and the anti-corrosion coating is a homemade Cu / ZnO-chitosan-pullulan coating. The preparation method of the Cu / ZnO-chitosan-pullulan coating comprises the following steps:
[0037] (1) 3 g of chitosan, 2 g of pullulan, and 1.25 g of cinnamaldehyde were dissolved in 300 mL of 1% acetic acid solution, heated in a 60° C. water bath with stirring for 3 h to obtain a chitosan-pullulan solution.
[0038] (2) 0.0361 g of copper acetate and 0.2 g of polyvinyl pyrrolidone were dissolved in 80 mL of diethylene glycol, and the mixture was stirred at 50 ° C for 30 min. 0.1806 g of whisker-like ZnO was added, and then 20 mL of thiourea solution was slowly poured in. At the same time, all the chitosan-pullulan solution prepared in step (1) and 2 mL of glycerol were added. The mixture was stirred at 120 ° C for 30 min and then cooled to 25 ° C to obtain a Cu / ZnO-chitosan-pullulan mixed solution.
[0039] (3) Soaking the Cryptomeria fortunei leaves in the Cu / ZnO-chitosan-pulullan mixed solution obtained in step (2) for 6 hours, and drying them at 25° C. for 24 hours to obtain Cryptomeria fortunei leaves with an antiseptic coating.
[0040] The sand layer mixed with discarded mask fragments, the earrings and metal strips of the discarded masks have been removed, and have been treated with ultraviolet sterilization. The main component is polypropylene; the fragments are 13mm long and 5mm wide; the overall thickness of the sand layer is 27.5cm, and the discarded mask fragments are mixed into the sand in an intermittent manner, that is, a 2.5cm layer of compacted discarded mask fragments is laid on each 2.5cm layer of compacted sand.
[0041] The rammed earth layer where the geothermal line is buried will be washed twice with clean water before laying. The geothermal line will heat the soil only in winter (November to February of the following year), and its power is 1kw; the geothermal line is buried at 1 / 2 the depth of the soil layer, and is arranged in an S shape with 1 / 2 the width of the trail. The area where the geothermal line is laid is equal in length to the edges of both sides of the trail, and the distance from the edges of both sides is 0.30m; the temperature is controlled at 25℃ with an automatic temperature controller, and the temperature control probe is inserted in the sand layer; the thickness of the rammed earth layer is 25cm.
[0042] Example 2
[0043] A design method for a forest health trail assembly, characterized in that the forest trail is divided into three layers in total, including, from top to bottom, a leaf layer with an anti-corrosion coating, a sand layer mixed with discarded mask fragments, and a rammed soil layer for burying geothermal lines. The leaf layer is on the ground, and the other two layers are buried underground. The trail is 1 m wide, and in addition, drainage ditches with a width of 8 cm and a slope height of 8 cm are designed on both sides of the trail.
[0044] The leaves in the leaf layer with the anti-corrosion coating are Cryptomeria fortunei leaves, the thickness of the leaf layer is 3 cm, and the anti-corrosion coating is a homemade Cu / ZnO-chitosan-pullulan coating. The preparation method of the Cu / ZnO-chitosan-pullulan coating comprises the following steps:
[0045] (1) 3 g of chitosan, 2 g of pullulan, and 1.25 g of cinnamaldehyde were dissolved in 300 mL of 1% acetic acid solution, heated in a 58° C. water bath with stirring for 3.5 h to obtain a chitosan-pullulan solution.
[0046] (2) 0.0857 g of copper acetate and 0.2 g of polyvinyl pyrrolidone were dissolved in 80 mL of diethylene glycol, and the mixture was stirred at 48 ° C for 32 min. 0.4286 g of whisker-like ZnO was added, and then 20 mL of thiourea solution was slowly poured in. At the same time, all the chitosan-pullulan solution prepared in step (1) and 2 mL of glycerol were added. The mixture was stirred at 115 ° C for 32 min and then cooled to 22 ° C to obtain a Cu / ZnO-chitosan-pullulan mixed solution.
[0047] (3) Soaking the Cryptomeria fortunei leaves in the Cu / ZnO-chitosan-pulullan mixed solution obtained in step (2) for 7 hours, and drying them at 22° C. for 26 hours to obtain Cryptomeria fortunei leaves with an antiseptic coating.
[0048] The sand layer mixed with discarded mask fragments, the earrings and metal strips of the discarded masks have been removed, and have been treated with ultraviolet sterilization. The main component is polypropylene; the fragments are 12mm long and 2mm wide; the overall thickness of the sand layer is 20cm, and the discarded mask fragments are mixed into the sand in an intermittent manner, that is, a 2cm layer of compacted discarded mask fragments is laid on each 3cm layer of compacted sand.
[0049] The rammed earth layer where the geothermal line is buried will be washed once with clean water before laying. The geothermal line will heat the soil only in winter (November to February of the following year), and its power is 1kw; the geothermal line is buried at 1 / 2 the depth of the soil layer, and is arranged in an S shape with 1 / 2 the width of the trail. The area where the geothermal line is laid is of equal length from the edges of both sides of the trail, and the distance from both sides is 0.25m; the temperature is controlled at 20℃ with an automatic temperature controller, and the temperature control probe is inserted in the sand layer; the thickness of the rammed earth layer is 20cm.
[0050] Example 3
[0051] A design method for a forest health trail combination, characterized in that the forest trail is divided into three layers in total, including, from top to bottom, a leaf layer with an anti-corrosion coating, a sand layer mixed with discarded mask fragments, and a rammed soil layer for burying geothermal lines. The leaf layer is on the ground, and the other two layers are buried underground. The trail is 1.5 m wide, and in addition, drainage ditches with a width of 10 cm and a slope height of 10 cm are designed on both sides of the trail.
[0052] The leaves in the leaf layer with the anti-corrosion coating are Cryptomeria fortunei leaves, the thickness of the leaf layer is 5 cm, and the anti-corrosion coating is a homemade Cu / ZnO-chitosan-pululan coating. The preparation method of the Cu / ZnO-chitosan-pululan coating includes the following steps:
[0053] (1) 3 g of chitosan, 2 g of pullulan, and 1.25 g of cinnamaldehyde were dissolved in 300 mL of 1% acetic acid solution, heated in a 65° C. water bath with stirring for 2.5 h to obtain a chitosan-pullulan solution.
[0054] (2) Dissolve 0.2 g of copper acetate and 0.2 g of polyvinyl pyrrolidone in 80 mL of diethylene glycol, stir magnetically at 52 °C for 28 min, add 1 g of whisker-like ZnO, and then slowly pour in 20 mL of thiourea solution. At the same time, add all the chitosan-pullulan solution prepared in step (1) and 2 mL of glycerol. Stir at 125 °C for 28 min and then cool to 28 °C to obtain a Cu / ZnO-chitosan-pullulan mixed solution.
[0055] (3) Soaking the Cryptomeria fortunei leaves in the Cu / ZnO-chitosan-pulullan mixed solution obtained in step (2) for 8 hours, and drying them at 28° C. for 22 hours to obtain Cryptomeria fortunei leaves with an antiseptic coating.
[0056] The sand layer mixed with discarded mask fragments, the earrings and metal strips of the discarded masks have been removed, and have been treated with ultraviolet sterilization. The main component is polypropylene; the fragments are 15mm long and 6mm wide; the overall thickness of the sand layer is 30cm, and the discarded mask fragments are mixed into the sand in an intermittent manner, that is, a 3cm layer of compacted discarded mask fragments is laid on each 2cm layer of compacted sand.
[0057] The rammed earth layer where the geothermal line is buried will be washed three times with clean water before laying. The geothermal line will heat the soil only in winter (November to February of the following year), and its power is 1kw; the geothermal line is buried at 1 / 2 the depth of the soil layer, and is arranged in an S shape with 1 / 2 the width of the trail. The area where the geothermal line is laid is of equal length from the edges of both sides of the trail, and is 0.38m away from the edges of both sides; the temperature is controlled at 22℃ with an automatic temperature controller, and the temperature control probe is inserted in the sand layer; the thickness of the rammed earth layer is 30cm.
[0058] Comparative Example 1
[0059] In a method for designing a forest trail assembly, the forest leaf layer is not coated with an anti-corrosion coating. The rest is the same as in Example 1.
[0060] Comparative Example 2
[0061] In a method for designing a forest trail assembly, no Cu / ZnO is added to the anti-corrosion coating in the forest leaf layer. The rest is the same as in Example 1. The anti-corrosion coating is prepared as follows:
[0062] (1) 3 g of chitosan, 2 g of pullulan, and 1.25 g of cinnamaldehyde were dissolved in 300 mL of 1% acetic acid solution, heated in a 60° C. water bath with stirring for 3 h to obtain a chitosan-pullulan solution.
[0063] (2) Dissolve 0.2 g of polyvinyl thiocarbamide in 80 mL of diethylene glycol, stir magnetically at 50 ° C for 30 min, then slowly pour in 20 mL of thiourea solution, and simultaneously add all the chitosan-pullulan solution prepared in step (1) and 2 mL of glycerol, stir at 120 ° C for 30 min, and then cool to 25 ° C to obtain a chitosan-pullulan mixed solution.
[0064] (3) Soaking the Cryptomeria fortunei leaves in the Cu / ZnO-chitosan-pulullan mixed solution obtained in step (3) for 6 hours, and drying them at 25° C. for 24 hours to obtain Cryptomeria fortunei leaves with an antiseptic coating.
[0065] Comparative Example 3
[0066] In a method for designing a forest trail assembly, there are no discarded masks in the sand layer. The rest is the same as in Example 1.
[0067] Comparative Example 4
[0068] In a method for designing a forest trail assembly, the plain soil layer is not washed. The rest is the same as in Example 1.
[0069] Test methods and results
[0070] In the above-mentioned Examples 1 to 3 and Comparative Examples 1 to 4, the anticorrosive coatings in the Examples and Comparative Examples were used to test chemical composition, surface morphology, antibacterial properties, moisture absorption rate, etc.; the monoterpene release test was conducted on the leaves; and the corresponding soil layers were used to test permeability, elasticity, etc. For the relevant performance tests of the anticorrosive coating, a film-forming treatment is required. The specific operation is to pour the prepared anticorrosive coating mixture into a polytetrafluoroethylene plate and put it into a 90°C oven to dry and form a film.
[0071] 1. Chemical composition test: Nicolet iS10 spectrometer was used to detect the Fourier transform infrared spectrum of the sample (thin film, >0.5cm*0.5cm), and the sample was measured at a wave number of 400-4000cm -1 Infrared absorption spectrum within the range. All samples were accurately weighed to 1g, and the Cu content in the coating was determined using the "Determination of Metal Elements in Solid Waste by Inductively Coupled Plasma Mass Spectrometry" (HJ 766-2015).
[0072] Figure 2 , 3 The infrared spectra of Examples 1 to 3 and Comparative Example 2 are shown in Figure 1. The coatings prepared in Comparative Example 2 and Examples 1 to 3 have an infrared spectrum of 3320 cm -1 The broad peak at 2870 cm-1 corresponds to the stretching vibration of -OH. -1 The peak at 1635 cm corresponds to the stretching vibration of CH. -1 The peak at 1050 cm-1 corresponds to the C=O group of chitosan and the -OCO- group of pullulan. -1 The peak at 402 cm is the CO group of chitosan. -1 The appearance of a new absorption band corresponding to Zn-O indicates that zinc oxide is successfully loaded on the chitosan-pullulan coating. Cu may not have a corresponding peak in the infrared spectrum due to a small amount of addition, but combined with the Cu content test results in Table 1, it can be seen that Cu is successfully loaded in the coating. Therefore, the present invention successfully prepared a Cu / ZnO-chitosan-pullulan coating.
[0073] Table 1 Cu content in coatings of Examples 1 to 3 and Comparative Example 2
[0074]
[0075] 2. Surface morphology test: A scanning electron microscope (SU8010) was used to observe the surface morphology of the sample (about 1 cm*1 cm).
[0076] Figure 4 The SEM images of the coating samples of Example 2 and Comparative Example 2 show that the surface of the coating of Comparative Example 2 is slightly rough because the two high molecular polymers of chitosan and pullulan will produce slight phase separation in the solvent, and the surface of the coating shows a slight uneven phenomenon after drying. Compared with Comparative Example 2, a more obvious convex phenomenon appears on the surface of Example 2 because after adding zinc oxide, there are certain forces of different sizes between zinc oxide and water molecules and acetic acid molecules. When the coating is dried, while the water molecules and acetic acid molecules are volatilized, chitosan, pullulan, zinc oxide, etc. in the mixed solution appear layered deposition phenomena, making the convex phenomenon of the coating surface of Example 2 obvious. In addition, although the surface of Example 2 is more obviously convex, there is no obvious phenomenon of large-scale aggregation, indicating that the dispersion of ZnO in the coating is relatively uniform; the coating surface appears convex accumulation phenomenon, indicating that the pores of the coating are increased, which is conducive to enhancing the air permeability and moisture absorption performance of the coating. Therefore, the present invention successfully obtains Cu / ZnO-chitosan-pululan coating.
[0077] 3. Antibacterial test: Cut the sample coating into 2.5cm×1.5cm pieces. Take 2 pieces as parallel samples and stick them on slides of the same size with silicone. Take another clean slide for parallel processing. Sterilize the coating sample and the blank group, then put them into 50mL liquid culture medium, and introduce 20mL Escherichia coli (10 -5 CFU / mL) and cultured in a constant temperature shaker at 37°C for 4 hours. Use a pipette to transfer 100ul of the above bacterial solution to the solid culture medium, spread it evenly with a coating rod, and then place it at 37°C.
[0078] Constant temperature incubator
[0079] The cells were cultured for 24 h and the number of colonies was finally observed.
[0080] Considering that Cryptomeria fortunei leaves are easy to corrupt, the present invention prepares an anticorrosive coating, wherein chitosan has certain antibacterial properties, but in view of its limited antibacterial ability, Cu-loaded whisker-like ZnO is added to the coating to synergistically exert antibacterial effects with chitosan. Figure 5The antibacterial test results of the coatings of Examples 1 to 3 and Comparative Example 2 are shown in the figure. The addition of chitosan in the coating sample of Comparative Example 2 makes the coating have a certain antibacterial effect, and its colony count is obviously less than that of the blank group, but its antibacterial effect is limited. Compared with Comparative Example 2, the antibacterial rate of Examples 1 to 3 reaches 100%, because the coatings of Examples 1 to 3 are loaded with Cu / ZnO, wherein ZnO produces active oxygen under photocatalysis, and active oxygen can destroy the organic matter of the microorganism itself and cause its death. In addition, ZnO can precipitate a small amount of free zinc ions under humid conditions (such as rain and muggy leaves producing water, etc.), and the zinc ions can interact with the negative charges on the surface of the surrounding bacteria, affecting the normal growth activities of the bacteria to achieve the antibacterial effect. In addition, the whisker-shaped ZnO is different from the traditional ZnO, and its needle tip with nano effect will not produce agglomeration, and it is a dispersible nano material, which is more conducive to the performance of its antibacterial properties. In addition, the presence of Cu in the coating of the present invention has a strong antibacterial effect, which can solve the problem that the antibacterial effect of ZnO is reduced under lightless conditions. Therefore, Cu, ZnO and chitosan work synergistically to greatly increase the antibacterial effect of the coating, and the Cu / ZnO-chitosan-pullulan coating prepared by the present invention has a good antibacterial effect.
[0081] 4. Moisture absorption rate: Cut the sample coating into 1cm×1cm pieces. Take 2 pieces as parallel samples, weigh each piece of coating accurately and mark it in m. i , place it in a petri dish in the natural environment indoors, record the indoor humidity every day, and measure its corresponding mass every 24 hours and record the data m f , until its mass remains basically unchanged to complete the experiment. A ) The calculation method is as follows: W A =(m f -m i ) / m i ×100%
[0082] Table 2 Indoor humidity recording results
[0083] Day 1 Day 2 Day 3 Day 4 Day 5 Day 6 humidity 35% 34% 50% 52% 51% 50%
[0084] Figure 6 The results show that the coating samples of Example 2 and Example 1 have certain moisture absorption performance. After being placed in the environment for 24 hours, the moisture absorption rate of the coating of Example 1 and Example 3 is higher than that of Comparative Example 2. Figure 4Scanning electron microscope image, the reason for the higher moisture absorption rate of the embodiment is that after adding Cu / ZnO, the surface of the embodiment is obviously convex, a small amount of accumulation phenomenon occurs, more water storage space is generated, which is more conducive to water retention, and a layer of "water barrier" can be formed on the surface of the blade, which has a certain slow release effect on the release of beneficial gases in the blade, and to a certain extent avoids the release of beneficial gases too quickly at the beginning. The moisture absorption rate of the coatings of all groups measured at 48h decreased because the accumulation space collapsed, causing the water in the coating to overflow again, which is conducive to the rapid volatilization of the remaining beneficial gases in the blade. In addition, the moisture absorption rate of the coatings of all groups on and after the third day re-presents a slow upward trend, because the environmental humidity on and after the third day is higher than the previous two days, which improves the water absorption capacity of the coating, and the reappearance of the water protective layer on the surface of the blade avoids the release of beneficial gases in the blade too quickly when the environmental humidity is high. And after the fifth day, the moisture absorption rates of Examples 1 and 3 are lower than those of Comparative Example 2, and the moisture absorption rate of Example 1 has no upward trend, which can avoid excessive water absorption to a certain extent, affecting the release of beneficial gases inside the blade. Therefore, the Cu / ZnO-chitosan-pululan coating prepared by the present invention has a certain moisture absorption performance, plays a certain regulatory role in the release of beneficial gases in the leaves, and can avoid the large-scale release of beneficial gases in fresh leaves and when the environmental humidity is high to a certain extent. The collapse of the accumulation space is also conducive to the rapid release of the remaining beneficial gases in the leaves in the later stage.
[0085] 5. Monomer ene release test: Since the volatile organic compounds released by Cryptomeria fortunei leaves are mainly monoterpenes, the relative content of sesquiterpenes is less than 1 / 10 of that of monoterpenes, so this experiment only tests the monoterpene content in the leaves. The release of monoterpenes from leaves was measured by the environmental chamber method. The volume of the small environmental chamber used in the experiment was 90L, and the parameter values of the environmental chamber were adjusted according to the experimental requirements. 30g of leaf samples of Examples 1 to 3 and Comparative Examples 1 to 4 of similar size were taken and placed in an environmental chamber set under certain conditions, and the Tenax tube was placed at the outlet of the sampling system for sampling at regular intervals. The sampling time was 90min, and the airflow rate was 1L / min. The monoterpene content was then determined by thermal desorption-gas chromatography / mass spectrometry. In addition, 4 portions of 30g of leaves from Comparative Example 1 were taken, and the temperature and humidity of the environmental chamber were adjusted. After the leaves were adapted to the environment for 2h, the monoterpene release was determined.
[0086] Table 3 Changes of monoterpene content released from leaves with the number of days
[0087]
[0088]
[0089] Table 3 shows the change of monoterpene content released from leaves in Examples 1 to 3 and Comparative Examples 1 to 2 over the number of days. The results show that on the 1st and 3rd days, since the surface coating of Examples 1 to 3 and Comparative Example 2 enhances the water absorption capacity when the humidity is high, a "water barrier" is formed on the surface of the leaves, which is beneficial to the slow release of beneficial gases in the leaves. Therefore, the release rate of monoterpene in the leaves of Examples 1 to 3 and Comparative Example 2 is lower than that of Comparative Example 1. In addition, as the number of days changes, the monoterpene release of the leaves of Examples 1 to 3 shows a trend of slow decrease, and the monoterpene release is higher than that of the comparative example after the 5th day, indicating that the coating on the surface of the example has a certain slow release effect; the leaves of Comparative Example 1 have no anticorrosive coating, and at the beginning of the experiment, the monoterpene release rate is fast, but as the number of days increases, after the leaves are corrupted on the 5th day, the monoterpene release is greatly reduced, and the degree of leaf corruption is further deepened on the 9th day, at this time, almost no monoterpene is released; Cu / ZnO is not added to the leaf anticorrosive coating of Comparative Example 2, and the antibacterial property of chitosan alone is weak. As the number of experimental days increases, the leaves are corrupted, which affects the release of monoterpene. After the leaves are corrupted on the 5th day, the release of monoterpene decreases significantly. Therefore, the leaf anticorrosive coating prepared by the present invention has good air permeability and anticorrosive properties.
[0090] Table 4 Effects of environmental conditions on the release of monoterpenes from leaves
[0091]
[0092]
[0093] Table 4 shows the release of monoterpenes from the leaves of Comparative Example 1 under different environmental conditions. The results show that temperature and humidity have a great influence on the release of monoterpenes. The increase of temperature and humidity increases the diffusion coefficient of gases such as monoterpenes. In addition, compared with humidity, the influence of temperature is slightly greater. Therefore, the present invention adopts the condition of low temperature and low humidity in winter to heat the trail, and due to the coverage of the leaf layer of Cryptomeria fortunei on the soil surface, water vapor is formed to increase the humidity of the environment around the leaves, thereby appropriately increasing the release of monoterpenes. In addition, the monoterpenes and other gases in the leaf layer can move upward under the thrust of the water vapor diffusing upward in the sand layer, thereby improving the effective utilization rate of beneficial gases to a certain extent.
[0094] 6. Tests on permeability, elasticity and unconfined compressive strength of sandy soil layers:
[0095] (1) The permeability test uses a constant head permeameter (TST-70 model). The dry soil samples are loaded into the instrument in layers and compacted layer by layer. After each layer is loaded, water is introduced from the regulating tube to the top surface of the sample to remove the bubbles in the sand. The last layer should be 3 to 4 cm higher than the upper pressure measuring tube hole, and 2 cm of gravel should be laid on the top surface of the sample as a buffer layer. The hydraulic slope is controlled by changing the height of the regulating tube. To improve data accuracy, the water level of the instrument should be controlled at a stable constant water level. The test was carried out at room temperature. In order to eliminate the influence of temperature, the indoor water temperature was measured during the test, and the test results were corrected to the permeability coefficient at a water temperature of 20°C.
[0096] (2) Elasticity test: A TCK-1 strain-controlled triaxial apparatus was used for triaxial compression test. The confining pressure was set to 200 kPa and the loading rate was 0.80 mm / min. The test was stopped when the axial strain reached 16%.
[0097] (3) Unconfined compressive strength test: The test was carried out on a TSZ-10 fully automatic triaxial tester in accordance with the standard for geotechnical test methods, with loading at a rate of 1 mm / min until the specimen was damaged.
[0098] Table 5 Test results of permeability, elasticity and unconfined compressive strength of sand layer
[0099]
[0100] Table 5 shows the test results of the permeability, elasticity, and unconfined compressive strength of the sandy soil layer of Examples 1 to 3 and Comparative Examples 1 to 4. The tested sandy soil layers were all heated in the trail assembly for 12 hours. It can be seen from the test results of Table 3 that the sandy soil layers of Examples 1 to 3 and Comparative Examples 1 to 2 have good permeability, elasticity, and unconfined compressive strength because the sandy soil layer is mixed with the discarded mask fragments after disinfection, so that the fibers are evenly distributed in the sandy soil. The fibers in the mask are connected by a group of monofilament fibers, which can allow moisture to enter the available space in its structure, thereby eliminating excess moisture in the sandy soil and reducing the pore water pressure of the sandy soil, thereby enhancing the permeability of the sandy soil layer. In addition, the discarded mask itself is composed of polypropylene, which has excellent mechanical properties. Mixing it with sandy soil improves the elasticity and unconfined compressive strength of the sandy soil layer. The sand layer of Comparative Example 3 has no mask fragments added, so its permeability, elasticity, and unconfined compressive strength are all reduced. The plain soil of Comparative Example 4 has not been washed, and the elasticity, permeability, and unconfined compressive strength of the sand layer have slightly decreased. This may be because there is a small amount of metal salt in the unwashed plain soil. When heated, the metal salt will penetrate upward, which will accelerate the aging of the mask fiber in the sand layer, thereby affecting the elasticity, permeability, and unconfined compressive strength of the sand layer. Therefore, the sand layer designed by the present invention has good permeability, elasticity, and unconfined compressive strength, which can ensure the stability of the trail.
[0101] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that are not conceived through creative work should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope defined in the claims.
Claims
1. A design method for a forest health trail assembly, characterized in that: The forest trail is divided into three layers in total. From top to bottom, there are a layer of leaves with anti-corrosion coating, a layer of sand and soil mixed with discarded mask fragments, and a layer of compacted soil where geothermal lines are buried. The leaf layer is the above-ground layer, and the sand and soil layers are the underground layers.
2. The leaf layer with anticorrosive coating as claimed in claim 1, characterized in that: The leaves are Cryptomeria fortunei leaves, the thickness of the leaf layer is 3 to 5 cm, and the anticorrosive coating is a homemade Cu / ZnO-chitosan-pulullan coating.
3. The Cu / ZnO-chitosan-pullulan coating according to claim 2, characterized in that: The method for preparing the coating comprises the following steps: S1: Dissolve chitosan, pullulan and cinnamaldehyde in acetic acid solution, heat in a water bath at 58-65°C and stir for 2.5-3.5h to obtain a chitosan-pullulan solution. The mass ratio of chitosan, pullulan and cinnamaldehyde is 1:(0.5-0.8):(0.35-0.45), The ratio of the mass (g) of the chitosan to the volume (mL) of the acetic acid solution is 1:(95-105), and the volume fraction of the acetic acid solution is 1%; S2: Dissolve copper acetate and polyvinyl pyrrolidone in diethylene glycol, stir magnetically at 48-52°C for 28-32 minutes, add whisker-like ZnO, slowly pour in thiourea solution, and simultaneously add all the chitosan-pullulan solution prepared in step S1 and a small amount of glycerol, stir at 115-125°C for 28-32 minutes, and then cool to 22-28°C to obtain a Cu / ZnO-chitosan-pullulan mixed solution. The mass ratio of the copper acetate, polyvinyl pyrrolidone and whisker-shaped ZnO is 1: (0.9-5.8): (4.8-5.2), The ratio of the volume of thiourea (L): the volume of diethylene glycol (L): the mass of copper acetate (g): the volume of glycerol (L) is 1: (3.8-4.2): (1.8-10): (0.08-0.12); S3: Soak the Cryptomeria fortunei leaves in the Cu / ZnO-chitosan-pulullan mixed solution obtained in step S2 for 6 to 8 hours, and dry them at 22 to 28° C. for 22 to 26 hours to obtain Cryptomeria fortunei leaves with an antiseptic coating.
4. The sand layer mixed with discarded mask fragments as claimed in claim 1, characterized in that: The earrings and metal strips in the discarded mask fragments have been removed and have been sterilized. The main component of the discarded masks is polypropylene. The fragments are 12 to 15 mm long and 2 to 6 mm wide. The overall thickness of the sand layer is 20 to 30 cm. The discarded mask fragments are mixed into the sand in an intermittent manner, and a 2 to 3 cm layer of compacted discarded mask fragments is laid on each 2 to 3 cm layer of compacted sand.
5. The rammed soil layer for burying geothermal wires according to claim 1, characterized in that: The bare soil will be washed with clean water 1 to 3 times before laying. The geothermal line is only used to heat the soil in winter (November to February of the following year), and its power is 1kw. The geothermal line is buried at 1 / 2 the depth of the bare soil layer, and is arranged in an S shape with 1 / 2 the width of the trail. The area where the geothermal line is laid is equal in length to the edges of both sides of the trail. The temperature is controlled at 20-25°C with an automatic temperature controller, and the temperature control probe is inserted in the sand layer. The thickness of the bare soil rammed layer is 20-30cm.
6. The design method of the forest health trail assembly as claimed in claim 1, characterized in that: Drainage ditches are provided on both sides of the forest health trail complex.